Alzheimer Disease: Crosstalk between the Canonical Wnt/Beta-Catenin Pathway and PPARs Alpha and Gamma - Vallée, Alexandre; Lecarpentier, Yves (Frontiers in Neuroscience, 2016)
The molecular mechanisms underlying the pathophysiology of Alzheimer's disease (AD) are still not fully understood. In AD, Wnt/beta-catenin signaling has been shown to be downregulated while the peroxisome proliferator-activated receptor (PPAR) gamma (mARN and protein) is upregulated. Certain neurodegenerative diseases share the same Wnt/beta-catenin/PPAR gamma profile, such as bipolar disorder and schizophrenia. Conversely, other NDs share an opposite profile, such as amyotrophic lateral sclerosis, Parkinson's disease, Huntington's disease, multiple sclerosis and Friedreich's ataxia. AD is characterized by the deposition of extracellular Abeta plaques and the formation of intracellular neurofibrillary tangles in the central nervous system . Activation of Wnt signaling or inhibition of both glycogen synthase kinase-3beta and Dickkopf 1, two key negative regulators of the canonical Wnt pathway, are able to protect against Abeta neurotoxicity and to ameliorate cognitive performance in AD patients. Although PPAR gamma is upregulated in AD patients, and despite the fact that it has been shown that the PPAR gamma and Wnt/beta catenin pathway systems work in an opposite manner, PPAR gamma agonists diminish learning and memory deficits, decrease Abeta activation of microglia, and prevent hippocampal and cortical neurons from dying. These beneficial effects observed in AD transgenic mice and patients might be partially due to the anti-inflammatory properties of PPAR gamma agonists. Moreover, activation of PPAR alpha upregulates transcription of the alpha-secretase gene and represents a new therapeutic treatment for AD. This review focuses largely on the behavior of two opposing pathways in AD, namely Wnt/beta-catenin signaling and PPAR gamma. It is hoped that this approach may help to develop novel AD therapeutic strategies integrating PPAR alpha signaling.